Partner influences on ICT use variety among middle-aged and older adults: The role of need for cognition. (January 2022) - Chopik, William J.; Francis, Jess
Abstract: This exploratory study examined individual and dyadic predictors of variety of ICT use. Need for cognition is associated with engaging in a variety of intellectually stimulating practices and a prominent individual difference predictor of the types of ICTs people use. Participants were a subset of 542 heterosexual couples ( N  = 1084 individuals; 50% women; M age  = 63.65; 83.9% Caucasian) from the Health and Retirement Study with access to the internet. Individuals high in need for cognition were more likely to use ICTs for a variety of reasons. Being married to someone high in need for cognition was associated with a greater variety of ICT ownership, use of ICTs for financial/transactional activities, and use of ICTs for miscellaneous reasons (e.g., research), although these effects were relatively small and the evidence for partner effects was relatively weak according to the distribution of p-values. Partner effects were not significant for social technology or internet-enabling ICTs; cross-partner interactions provided suggestive evidence for compensatory partner effects of need for cognition. Findings are discussed with respect to the relational and contextual determinants of ICT use in older adulthood. Highlights: Past research identified many individual predictors of varied ICT use; few studies have examined partner characteristics. Having a partner high in NFC was associated with more variety in ICT ownership, ICT financial use, and miscellaneous ICT use. Partner NFC was not significantly associated with the variety of using social technology and internet-enabling ICTs. Having a partner high in NFC compensated for having low levels of NFC among individuals. This exploratory study found relatively weak but suggestive evidence for partner influences on variety of ICT use.